Electrodeposited NixCo3−xO4 nanostructured films as bifunctional oxygen electrocatalysts1. Issue 46 (11th June 2015) - Lambert, Timothy N.; Vigil, Julian A.; White, Suzanne E.; Davis, Danae J.; Limmer, Steven J.; Burton, Patrick D.; Coker, Eric N.; Beechem, Thomas E.; Brumbach, Michael T.
<x xml:space="preserve">Abstract</x> Nanostructured NixCo3−xO4 films serve as effective electrocatalysts for both the oxygen reduction reaction and oxygen evolution reaction in alkaline electrolyte.